Pengaruh Disiplin Terhadap Kemandirian Belajar Siswa Kelas IV SD Muhammadiyah Kreatif Kraksaan Kabupaten Probolinggo - Mukti Peni Indriawati; Muhishah Hidayati; Kiky Fatmawati; Benny Prasetya (Education Reserach Center, 2026)
Independent learning is an essential competence that needs to be developed from the elementary school level to support students’ long-term academic success. One factor assumed to influence independent learning is learning discipline. This study aimed to examine the effect of learning discipline on independent learning among fourth-grade students at SD Muhammadiyah Kreatif Kraksaan, Probolinggo Regency, and to determine the extent of its contribution. This research employed a quantitative approach using an explanatory associative method. The population consisted of 32 fourth-grade students, and a saturated sampling technique was applied. Data were collected through Likert-scale questionnaires that had been tested for validity and reliability. Data analysis involved descriptive statistics, Pearson correlation, and simple linear regression using SPSS version 27. The results showed that learning discipline had a positive and significant effect on students’ independent learning (t = 2.385; Sig. = 0.024 < 0.05). The coefficient of determination (R² = 0.159) indicated that learning discipline contributed 15.9% to the variation in independent learning. These findings highlight the importance of strengthening learning discipline to foster independent learning in elementary school students.